2022
DOI: 10.1021/acsami.2c06957
|View full text |Cite
|
Sign up to set email alerts
|

Adropin Carried by Reactive Oxygen Species-Responsive Nanocapsules Ameliorates Renal Lipid Toxicity in Diabetic Mice

Abstract: Diabetic kidney disease (DKD) is a common diabetes complication mainly caused by lipid toxicity characterized by oxidative stress. Studies have shown that adropin (Ad) regulates energy metabolism and may be an effective target to improve DKD. This study investigated the effect of exogenous Ad encapsulated in reactive oxygen species (ROS)-responsive nanocapsules (Ad@Gel) on DKD. HK2 cells were induced with high glucose (HG) and intervened with Ad@Gel. A diabetes mouse model was established using HG and high-fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…In addition, other researchers found that Nox4 knockdown reduced NADPH oxidase activity, accompanied by reduction in high-glucose-induced superoxide, yet mitochondrial Nox4 expression was increased in the renal cortex of diabetic rats, demonstrating the role for Nox4 in the regulation of mitochondrial function ( 144 ). Adropin improved lipid metabolism and renal function in diabetic mice, regulated blood glucose and lipids, inhibited ROS production, improved lipid deposition and down-regulated lipoprotein expression ( 145 ). G Protein-Coupled Bile Acid Receptor TGR5 improved indicators of renal injury in db/db mice, upregulated regulators of mitochondrial biogenesis, reduced lipid accumulation and H 2 O 2 production and increased SOD2 activity; similarly, similar results were observed in high glucose-induced podocytes ( 146 ).…”
Section: The Relationship Between Oxidative Stress-induced Mitochondr...mentioning
confidence: 99%
“…In addition, other researchers found that Nox4 knockdown reduced NADPH oxidase activity, accompanied by reduction in high-glucose-induced superoxide, yet mitochondrial Nox4 expression was increased in the renal cortex of diabetic rats, demonstrating the role for Nox4 in the regulation of mitochondrial function ( 144 ). Adropin improved lipid metabolism and renal function in diabetic mice, regulated blood glucose and lipids, inhibited ROS production, improved lipid deposition and down-regulated lipoprotein expression ( 145 ). G Protein-Coupled Bile Acid Receptor TGR5 improved indicators of renal injury in db/db mice, upregulated regulators of mitochondrial biogenesis, reduced lipid accumulation and H 2 O 2 production and increased SOD2 activity; similarly, similar results were observed in high glucose-induced podocytes ( 146 ).…”
Section: The Relationship Between Oxidative Stress-induced Mitochondr...mentioning
confidence: 99%
“…This would indicate that presence of adropin may be required for priming the phosphorylation of eNOS and the production of NO through Akt activation, which is Ca 2+ -independent, to elicit augmented endothelial-dependent vasodilation. Alternatively, adropin has been reported to decrease reactive oxygen species (228), which could result in the increased bioavailability of NO and endothelial function of aged arteries. Third, the receptor for adropin-mediated effects on endothelial cells remains to be fully elucidated and controversial.…”
Section: Chapter 4: Summary and Future Directionsmentioning
confidence: 99%
“…Cancer cells use lipid metabolism to obtain energy, biofilm components, and signaling molecules needed for proliferation, survival, invasion, metastasis, tumor response, and cancer treatment. Numerous studies showed that lipid metabolism disorders play a key role in the progression of NPs exposure toxicity. ,− In this experimental group, 18-hydroxyoleate and 9,10-epoxystearic acid were up-regulated and phosphocholine was downregulated, while the levels of the remaining metabolites did not change significantly. Both metabolites in the GNR group were significantly up-regulated, implying that these may help in clearing cancer cells.…”
Section: Resultsmentioning
confidence: 99%